Art and Copyright - Stokes, Simon (Hart Publishing, 2021)
First published in 2001, Art and Copyright has established itself as a leading text in the field. Revised and updated, this third edition includes additional coverage of the following topics: the relationship between designs law and artistic works;EU and Brexit developments;AI-created works;graffiti and other non-conventional works;blockchain and rights management;orphan works;new exceptions to copyright; anddigital copyright, art databases and online platforms. This book remains an invaluable work for all those involved in art law and for intellectual property lawyers involved with the exploitation and/or sale of artistic works, as well as for intellectual property academics, researchers, law students, curators, publishers, artists, gallery owners, auction houses, and those developing and running online art platforms, databases and technology to transact in art.